Proximate and ultimate causes of variable visual sensitivities: insights from cichlid fish radiations - Carleton, Karen L. (Genesis, 2016)
Animals vary in their sensitivities to different wavelengths of light. Sensitivity differences can have fitness implications in terms of animals’ ability to forage, find mates and avoid predators. As a result, visual systems are likely selected to operate in particular lighting environments and for specific visual tasks. This review focuses on cichlid vision, as cichlids have diverse visual sensitivities, and considerable progress has been made in determining the genetic basis for this variation. We describe both the proximate and ultimate mechanisms shaping cichlid visual diversity using the structure of Tinbergen’s four questions. We describe 1) the molecular mechanisms that tune visual sensitivities including changes in opsin sequence and expression; 2) the evolutionary history of visual sensitivity across the African cichlid flocks; 3) the ontological changes in visual sensitivity and how modifying this developmental program alters sensitivities among species; and 4) the fitness benefits of spectral tuning mechanisms with respect to survival and mating success. We further discuss progress to unravel the gene regulatory networks controlling opsin expression and suggest that a simple genetic architecture contributes to the lability of opsin gene expression. Finally, we identify unanswered questions including whether visual sensitivities are experiencing selection, and whether similar spectral tuning mechanisms shape visual sensitivities of other fishes.